Aldo-Keto Reductases 1B in Endocrinology and Metabolism - Pastel, Emilie; Pointud, Jean-Christophe; Volat, Fanny; Martinez, Antoine; Lefrançois-Martinez, Anne-Marie (Frontiers in Pharmacology, 2012)
The aldose reductase (human AKR1B1/mouse Akr1b3) has been the focus of many research because of its role in diabetic complications. The starting point of these alterations is the massive entry of glucose in polyol pathway where it is converted into sorbitol by this enzyme. However, the issue of aldose reductase function in non-diabetic condition remains unresolved. Aldose reductase-like enzymes (AKR1B10, Akr1b7 and Akr1b8) are highly related isoforms often co-expressed with bona fide aldose reductase, making functional analysis of one or the other isoform a challenging task. AKR1B/Akr1b members share at least 65% protein identity and the general ability to reduce many redundant substrates such as aldehydes provided from lipid peroxidation, steroids and their by-products and xenobiotics in vitro. Based on these properties, AKR1B/Akr1b are generally considered as detoxifying enzymes. Considering that divergences should be more informative than similarities to help understanding their physiological functions, we chose to review specific hallmarks of each human/mouse isoforms by focusing on tissue distribution and specific mechanisms of gene regulation. Indeed, although the aldose reductase shows ubiquitous expression, aldose reductase-like proteins exhibit tissue-specific patterns of expression. We focused on 3 organs where certain isoforms are enriched, the adrenal gland, enterohepatic and adipose tissues and tried to connect recent enzymatic and regulation data with endocrine and metabolic functions of these organs. We presented recent mouse models showing unsuspected physiological functions in the regulation of glucido-lipidic metabolism and adipose tissue homeostasis. Beyond the widely accepted idea that AKR1B/Akr1b are detoxification enzymes, these recent reports provide growing evidences that they are able to modify or generate signal molecules. This conceptually shifts this class of enzymes from unenviable status of scavenger to upper class of messengers.